Study on Intuitionistic Fuzzy Abundant Semigroup - Ancy Varghese, Paul Isaac (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
We present some features of intuitionistic fuzzy subsets on an abundant semi- group in this study. Also presented the concept of intuitionistic fuzzy abundant semigroups, as well as some of its features.We also define homomorphism and investigate the image and inverse image of an intuitionistic fuzzy abundant semigroup when homomorphism is applied.